2018
DOI: 10.3390/toxins10100418
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability in the Development and Potential Toxicity of Phormidium Biofilms in the Tarn River, France

Abstract: Proliferation of Phormidium biofilms in rivers is becoming a worldwide sanitation problem for humans and animals, due to the ability of these bacteria to produce anatoxins. To better understand the environmental conditions that favor the development of Phormidium biofilms and the production of anatoxins, we monitored the formation of these biofilms and their toxins for two years in the Tarn River, biofilms from which are known to have caused the deaths of multiple dogs. As previously observed in New Zealand, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
1
14
3
Order By: Relevance
“…All samples were dominated by ATX and dhATX, and not HTX and dhHTX, which contrasts with observations elsewhere: dhATX, dhHTX and HTX typically dominate in New Zealand [8, 15], and in France ATX dominates [29], although dhATX has also been detected [30]. However, Anderson et al [19] used anatoxins in crude extracts of Microcoleus cultures isolated from the Russian river in their toxicological study and dhATX comprised > 99% of the anatoxins, demonstrating that there is likely large strain to strain variability in the variants produced.…”
Section: Discussioncontrasting
confidence: 75%
“…All samples were dominated by ATX and dhATX, and not HTX and dhHTX, which contrasts with observations elsewhere: dhATX, dhHTX and HTX typically dominate in New Zealand [8, 15], and in France ATX dominates [29], although dhATX has also been detected [30]. However, Anderson et al [19] used anatoxins in crude extracts of Microcoleus cultures isolated from the Russian river in their toxicological study and dhATX comprised > 99% of the anatoxins, demonstrating that there is likely large strain to strain variability in the variants produced.…”
Section: Discussioncontrasting
confidence: 75%
“…Loza, Berrendero, Perona, & Mateo, 2013; Loza, Perona, Carmona, & Mateo, 2013; Loza, Perona, & Mateo, 2013; Monteagudo & Moreno, 2016; Takano, Igarashi, Mikami, & Hino, 2003; Voorhies et al., 2012). Echenique‐Subiabre, Tenon, et al (2018) found that proliferations of Phormidium occurred with nitrate concentrations of 1.46 mg/L, whereas McAllister, Wood, Atalah, et al (2018) and Wood, Atalah, et al (2017) found that proliferations occurred when dissolved inorganic nitrogen concentrations were as low as 0.02 mg/L. Concentrations of dissolved reactive phosphorus in the water column below 0.05 mg/L have been shown to favour M. autumnalis proliferation over other periphyton in New Zealand streams (McAllister, Wood, Atalah, et al, 2018).…”
Section: Autecology Of Toxic Benthic Cyanobacteriamentioning
confidence: 99%
“…The general accrual cycle for benthic cyanobacteria typically involves: (1) initiation of a mat through colonisation by filaments or hormogonia that settle on a substrate, or regrowth of relic populations; (2) subsequent growth through increase in thickness, or lateral expansion; and (3) detachment of mats (Echenique‐Subiabre, Tenon, Humbert, & Quiblier, 2018; McAllister et al., 2016). After colonisation, the balance of growth‐ and loss‐promoting factors determines the length of the accrual cycle, and the size and persistence of the proliferation.…”
Section: Autecology Of Toxic Benthic Cyanobacteriamentioning
confidence: 99%
See 2 more Smart Citations